KEMISKINAN TRANSIEN DAN MASYARAKAT PEDESAAN PASCA BENCANA - Maulana Kurnia Putra (Universitas Sebelas Maret (UNS), 2021)
This paper study the context of poverty and empowerment efforts during the recovery period in disaster-affected rural communities in Rukem Hamlet, Purworejo Regency and Bobanehena Hamlet, West Halmahera Regency. The purpose of this study is to explain and provide additional perspectives in assisting the community during the recovery process through community empowerment indicators. This research is a case study with a qualitative method with the focus of analysis on mentoring and empowerment activities that become the strength of the post-disaster community to recover from an emergency quickly. The results of this study are: 1) fulfillment of the key elements of post-disaster community empowerment needed for communities to recover faster from transient poverty through mentoring activities; 2) To achieve the level of economic empowerment, community assistance is needed for qualitative problems in stages to make rural communities more empowered. With this research, there is the development of studies related to the performance of social work to respond to the issue of poverty and empowerment of rural communities in a post-disaster context so that program intervention designs can be more comprehensive.